PENGEMBANGAN STRATEGI PROMOSI ONLINE YUL GENDHIS BATIK PADA MASA NEW NORMAL - Hati, Talenta Elok; Hagijanto; Malkisedek, Malkisedek (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2022)
Yul Gendhis Batik (YGB) is one of the micro batik businesses engaged in the fashion sector. Since 2010 YGB has focused on selling offline because the advantages of selling offline are enough. However, from March to May 2020 when the Covid-19 virus entered Indonesia, YGB suffered heavy losses. Therefore, a breakthrough promotion strategy is needed in the form of online media that is more structured and well integrated so that YGB can sell and carry out promotions. Previously, an online media design for YGB had been carried out but the consumer purchase flow, design, and upload time were inconsistent. To design online media, data is needed, namely visual data through observations on YGB and its competitors, data about future plans, concepts and thoughts and consumer tastes obtained through interviews. Analysis using SWOT analysis. The results of the design are uploads to Instagram, websites, Facebook, and online catalogs on WhatsApp business. Through the results of this design, YGB can continue to grow and expand its business reach both through offline and online media.